1986
DOI: 10.1007/bf00499001
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphisms in north Sardinian newborns and their linkage with abnormal ? globin gene arrangements and with ?o-thalassemia

Abstract: Fetal hemoglobin analysis and globin gene mapping have identified one type of beta(0)-thalassemia and four different gamma globin gene arrangements among newborn babies from the northern part of Sardinia. The beta(0)-thalassemia with a nonsense mutation at codon 39 was found on two chromosomes, each with a distinct pattern of polymorphic restriction sites; one had the A gamma T (A gamma 75 Ile----Thr) mutation, while the second did not. Four closely related haplotypes were identified for chromosomes with the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It has already been described that the Sardinian fi°-thalassaem ic gene is closely linked with the mutated Ay ] gene, with a gene frequency o f 0.823 [9], This lin kage has been recently confirm ed by genomic blotting [4] which showed that /T'-thalassaem ic patients, AyT homozygotes, are also hom ozygotes for the haplotype II of Orkin et al [10], this haplotype being the most comm on am ong norm al Sardinian newborns hom o zygote for the AyT gene. On the contrary, p° hom ozy gotes without any AyT chains are homozygotes for the haplotype I, which is characteristic of the chrom o some bearing the norm al Ay' gene [4], The linkage be tween the p° and the AyT genes has also been described in homozygous patients from the M editerranean and other areas [2, 5-7, 11, 14], Similarly, a strong linkage has been observed between the P+ and the Ay' genes in homozygous thalassaemic patients of intermediate severity from Algeria, Sicily, Tunisia and Portugal [2, 16,18], The aim o f this work was to study the y chain com position of the foetal haemoglobin of Sardinian P+ -thalassaem ic patients in order to establish the pos sible linkage between the /J+ and the AyT genes in this population.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…It has already been described that the Sardinian fi°-thalassaem ic gene is closely linked with the mutated Ay ] gene, with a gene frequency o f 0.823 [9], This lin kage has been recently confirm ed by genomic blotting [4] which showed that /T'-thalassaem ic patients, AyT homozygotes, are also hom ozygotes for the haplotype II of Orkin et al [10], this haplotype being the most comm on am ong norm al Sardinian newborns hom o zygote for the AyT gene. On the contrary, p° hom ozy gotes without any AyT chains are homozygotes for the haplotype I, which is characteristic of the chrom o some bearing the norm al Ay' gene [4], The linkage be tween the p° and the AyT genes has also been described in homozygous patients from the M editerranean and other areas [2, 5-7, 11, 14], Similarly, a strong linkage has been observed between the P+ and the Ay' genes in homozygous thalassaemic patients of intermediate severity from Algeria, Sicily, Tunisia and Portugal [2, 16,18], The aim o f this work was to study the y chain com position of the foetal haemoglobin of Sardinian P+ -thalassaem ic patients in order to establish the pos sible linkage between the /J+ and the AyT genes in this population.…”
mentioning
confidence: 88%
“…These data suggest the presence of at least 2 /(+-thalassaemic chrom osom es in Sardinians, one associated with the variant AyT allele and one asso ciated with the norm al Ay*. The latter is prevalent am ong adult patients showing the interm ediate form of the thalassaem ic disease, which is not transfusion-dependent.The observation of the occurrence of the mutated Ay chain, known as the AyT chain, present in the socalled Hb F Sardinia (a 2A/ 275 lle-Thr) [3,5,13] in the foetal haem oglobin has been dem onstrated to be very im portant for our knowledge o f the genetics o f the ft gene cluster [5][6][7]14], The high incidence of the AyT al lele in various haematological disorders makes its product a m arker to be used for the evaluation o f the y chain production being in cis or in trans o f a particu lar gene [5], M oreover, a num ber of /) thalassaemia m utations have been found in chromosomes contain ing the AyT gene [2,4,9,16,18].In Sardinia, at least 2 main /(-thalassaemic genes coexist: the most com m on and widespread gene, characterized by a non-sense m utation at residue 39 [17], and the gene, present in the N orthern area of the island [8], not yet characterized at a m olecular lev el. It has already been described that the Sardinian fi°- , The linkage be tween the p° and the AyT genes has also been described in homozygous patients from the M editerranean and other areas [2, 5-7, 11, 14], Similarly, a strong linkage has been observed between the P+ and the Ay' genes in homozygous thalassaemic patients of intermediate severity from Algeria, Sicily, Tunisia and Portugal [2,16,18], The aim o f this work was to study the y chain com position of the foetal haemoglobin of Sardinian P+ -thalassaem ic patients in order to establish the pos sible linkage between the /J+ and the AyT genes in this population.…”
mentioning
confidence: 99%
“…During the course of studies for y-or /I-globin gene anomalies, including y-globin gene triplications or deletions [12][13][14], y-globin gene mutants [15,16], and /?-or 5/J-thalassemia [13,16], it was possible to quanti tate Hb A in cord blood samples from relatively large numbers of normal newborn babies from Italy (Sardi nia), Yugoslavia (Macedonia), Turkey (Adana), Ja pan (Kurashiki City), and China (Beijing). The possi- …”
Section: Adult Hb Levels In Newborn Babies From Different Countriesmentioning
confidence: 99%
“…but not in Blacks) [17,23]. Heterozygotes have Hb F with some 40% Gy chains and 60% Ay chains, while the two homozygotes (one Chinese and one Indian) had Hb F with Ay chains only [23].…”
mentioning
confidence: 99%
“…A relatively simple gene mapping technique, involving a Pst 1 di gest and hybridization with a probe recognizing the DNA between the two y genes, allows its detection [31 ]. Only heterozygotes (Chinese, Japanese, Mediter ranean, and Black) have been described; the Gy level in their cord bloods is a low 35-45% [16,17], (2) The -Gy-Ay-arrangement has been replaced by -c,y-c'y-which can readily be demonstrated when a Pst 1 digest of DNA is hybridized with the same in ter-;/ probe or with the yIVS-II probe [31]. The -GyGy-anomaly seems to occur at slightly higher fre quencies than the -Ay-Ay-abnormality; heterozygous babies have a Gy value of 80-90%, while the one hom ozygous black newborn had 100% Gy.…”
mentioning
confidence: 99%